2016
DOI: 10.1051/0004-6361/201527600
|View full text |Cite
|
Sign up to set email alerts
|

Shear-driven instabilities and shocks in the atmospheres of hot Jupiters

Abstract: Context. General circulation models of the atmosphere of hot Jupiters have shown the existence of a supersonic eastward equatorial jet. These results have been obtained using numerical schemes that filter out vertically propagating sound waves and assume vertical hydrostatic equilibrium, or were acquired with fully compressive codes that use large dissipative coefficients. Aims. We remove these two limitations and investigate the effects of compressibility on the atmospheric dynamics by solving the standard Eu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 47 publications
6
74
1
Order By: Relevance
“…Such a damping length could be either due to a horizontal Kelvin-Helmholtz instability or due to the steepening of day-night standing waves into shocks. We note that the shock-resolving simulations in Fromang et al (2016) also found a dominant scale for horizontal shear instabilities of L a 2 5 p , and are thus consistent with our results. The upper end of our wind speed estimate is additionally consistent with the bulk flow becoming supersonic, and thus prone to dissipation via shocks ( Figure 5).…”
Section: Evaluating Drag Mechanisms With Observationssupporting
confidence: 91%
“…Such a damping length could be either due to a horizontal Kelvin-Helmholtz instability or due to the steepening of day-night standing waves into shocks. We note that the shock-resolving simulations in Fromang et al (2016) also found a dominant scale for horizontal shear instabilities of L a 2 5 p , and are thus consistent with our results. The upper end of our wind speed estimate is additionally consistent with the bulk flow becoming supersonic, and thus prone to dissipation via shocks ( Figure 5).…”
Section: Evaluating Drag Mechanisms With Observationssupporting
confidence: 91%
“…As in Perez-Becker & Showman (2013), they showed that the combined effects of increasing relative efficacy of radiative cooling and increasing drag strength can explain the increase in dayside-nightside temperature contrast with increasing equilibrium temperature, as both mechanisms damp wave adjustment processes. This drag is likely due to either Lorentz forces in an ionized atmosphere threaded by a dipolar magnetic field (Perna et al 2010;Batygin et al 2013;Rauscher & Menou 2013;Rogers & Komacek 2014;Rogers & Showman 2014) or smallscale instabilities (Li & Goodman 2010;Youdin & Mitchell 2010;Fromang et al 2016), including shocks, which largely are expected to occur on the dayside of the planet (Heng 2012;Fromang et al 2016). However, Komacek & Showman (2016) found that drag only affects dayside-nightside temperature differences if it occurs on a characteristic timescale much shorter than the rotation period of the planet.…”
Section: Introductionmentioning
confidence: 99%
“…Our T85 and T127 runs do reach the latitudinal regime at which one might expect the dynamical transition witnessed by Fromang et al (2016) to manifest. However, as exemplified in the lower two panels of Figure 2, even at high resolution, we do not find any evidence for the oscillatory/cyclic behavior of the equatorial regions reported by Fromang et al (2016).…”
Section: Plasim-gen High Resolution Modelsmentioning
confidence: 62%
“…These results are worth discussing in the context of the study of Fromang et al (2016), who find a transition to a markedly different regime of circulation at latitudinal resolutions in excess of 64-128 cell elements (see their Figure 4). Our T85 and T127 runs do reach the latitudinal regime at which one might expect the dynamical transition witnessed by Fromang et al (2016) to manifest. However, as exemplified in the lower two panels of Figure 2, even at high resolution, we do not find any evidence for the oscillatory/cyclic behavior of the equatorial regions reported by Fromang et al (2016).…”
Section: Plasim-gen High Resolution Modelsmentioning
confidence: 79%
See 1 more Smart Citation